BAHASA, BISNIS, KOMUNITAS MULTIKULTURAL: REGISTER PADA INTERAKSI JUAL-BELI DI WARUNG SEMBAKO RUMBIA, LAMPUNG TENGAH - Ela Lolitasari (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2026)
This study aims to analyze the forms, functions of registers based on Halliday's theory, and aspects underlying the use of the register in one of the stalls in Rumbia District, Central Lampung, which is multicultural. The method applied in this study is a descriptive qualitative method, involving interviews and the Simak Bebas Libat Cakap (SBLC) technique to obtain relevant data. The data are in the form of utterances from sellers and buyers containing registers. The data are then analyzed and classified based on their form and function. Based on the analysis, the findings show that there are 19 (23,75%) monomorphemic registers and 61 (76,25%) polymorphemic registers. The register functions include 17 instrumental, 9 regulatory, 35 representative, 10 interaction, 3 personal, 2 heuristic, and 4 imaginative functions. These registers are predominantly derived from Javanese (82,5%) because the seller and the majority of buyers are Javanese. Registers tend to be used to explain the condition, type, and quantity of goods, as well as specific terms for an item. The use of registers is also adjusted based on social status, the buyer's language, social relationships, and the community's culture. Registering at Bek Ni's stall is not only for transactional interactions, but also to maintain social relationships, as a source of information, as a medium of expression, and to strengthen cultural and linguistic identity.